More Environmental Sustainability Routing and Energy Management for All Electric Ships - Pan, Xuewei; Zhu, Xingzhou; Zhao, Fei (Frontiers in Energy Research, 2022)
With the popularity of the electrification of marine transportation, strategic energy-saving and environment-friendly management is gaining more attention recently. This paper proposes a novel coordinated navigation routing and power generation scheduling model, which aims at making a compromise between investment cost, operation cost, and greenhouse gas emissions under the distributional robust ambiguity of photovoltaic. A maritime hybrid energy configuration that combines diesel generator (DG), battery energy storage system (BESS), fuel cell (FC), photovoltaic (PV), and the cold-ironing connection is presented with a real-world navigation routine from Dalian to Singapore, and the optimization problem is solved through a bi-level tri-objective differential evolution algorithm, where navigation parameters, ESS and FC capacity and weight between operation cost and emission functions, are optimized in the upper level and specific power generation scheduling is settled in the lower level. Six case studies are conducted to verify its effectiveness and accuracy, and the simulation results demonstrate the proposed method can further reduce the operation cost while minimizing air contamination.